O ruralismo pedagógico no estado de São Paulo nas décadas de 1930 e 1940: as escolas normais, os cursos de especialização, as escolas técnicas e os clubes agrícolas - Basso, Jaqueline Daniela (2018)
During the 1980s and 1940s were marked by the impact between those who defended the urbanization and industrialization of the countries, and the rural persons desired the maintenance of the agrarian economy and the power oligarchy. The rural movement gave origin to an educacional perspective, it was called Ruralist Pedagogical which was based on the defence for a specific education for rural areas, and in the credulity that it would be capable of possess the migratory process of the field for cities, it was inevitable in advance of technological development, transforming increasingly them to the urban areas in attractive, also comfort and availability of jobs places in trade and industries. In this work, the objective is understand, how the Ruralist Pedagogical movement materialized in São Paulo State and how regarding the initiatives directed the educational formation for the rural schools, in the decades of 1930 and 1940.Therefore, contemplate the following specific objectives: How one gave the development of the Normal Education in Brazil and São Paulo's State; understand, to develop effective responses in the Ruralist Pedagogical educational movement and the historical context that produced it in Brazil, also verify how Ruralist Pedagogical influenced the teacher training through the Normal Rural Schools and the Agricultural Specialization Courses. Likewise, to identify the influence of the Ruralist Pedagogical in the Vocational education offered in the Agricultural Schools for example the Esalq and, finally, to understand the Agricultural School Clubs, institutions implemented the ruralist pedagogical. Validated and contemplated the proposed objectives is based on primaries sources, such as legislation, official documents of the studied period, yearbooks of education, Digital Newspaper library available in San Carlos' Municipality, besides it the bibliographical review. The initiatives ruralist analyzed, demonstrated the ruralist pedagogical movement turned especially in activities agricultural practices, notions of hygiene in the curriculum of the Normal Rural Schools, Courses of Agricultural Specialization and Agricultural Clubs, it was an attempt for the ruralist in keeping the economic order agrarian by means of the fixation of people on the land. Finally, this investigation serves to contribute the writers on behalf of the history of the rural Brazilian education and paulista; regarding the educational formation.